A Study of the Impact of Qualification and Salary on the Attitude of Primary School Teachers towards the Teaching Profession - Sharma, Neha (EDUCARE, 2015)
ABSTRACT: The education at the primary level is the platform, where we prepare the knowledge base in the mind of the students; so, it is essential that the instructions given to them should be such which help them to internalize the concept to the optimum level possible, and the teacher is the one who can do this task efficiently. This study examined the attitude of primary school teachers towards the teaching profession. The sample was drawn with the help of Simple Random Sampling and Incidental Sampling. Firstly, the 14 primary schools were selected with the help of Simple Random Sampling and 201 teachers from these schools were selected with the help of Incidental Sampling from Aligarh City, Uttar Pradesh, India. The sample consisted of 201 primary school teachers selected from 14 primary schools of Aligarh City. Out of total sampled teachers 117 were trained and 84 were untrained. The distribution of total sampled teachers according to their salaries, 92 were found above INR (Rupee India) 5,000; and 109 were found below INR 5,000. The investigator used attitude scale developed by M.R. Verma (1972) to assess the attitude of primary school teachers towards teaching profession. The obtained data were analyzed by calculating mean, standard deviation, and two-way ANOVA (Analysis of Variance). The result indicated that salary have a significant impact on the attitude of teachers towards teaching profession, whereas the qualification does not bring any impact on the same and the interaction effect of qualification and salary on the attitude of primary school teachers found to be non-significant.KEY WORDS: Attitude, primary level, aims of education, teaching profession, teaching practice, salary, qualification, and significant and non-significant impact.About the Author: Neha Sharma is a Research Scholar at the Department of Education AMU (Aligarh Muslim University) in Aligarh, Uttar Pradesh, India. For academic purposes, the author are able to be contacted via phone at: 91-9456242258 or via e-mail at: nehaasharma123@gmail.comHow to cite this article? Sharma, Neha. (2015). âA Study of the Impact of Qualification and Salary on the Attitude of Primary School Teachers towards the Teaching Professionâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.55-62. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (June 21, 2015); Revised (July 23, 2015); and Published (August 25, 2015).